Kunst in der Stadt Hamburg : 40 Werke im öffentlichen Raum - Abele, Isabelle; Bandyopadhyay, Papia; Dinse, Ulrike; Dziacka, Agata; Eichhorn, Nadine; Fleckner, Uwe; Glozer, Franziska; Kalenbach, Nina; Pora, Raluca; Steinkamp, Maike; Tieskötter, Ruth; Waller, Stefan (Berlin Hamburg : Nicolaische Verlagsbuchhandlung Berlin, 2007)
Balkenhol, Stephan ; Clegg & Guttmann ; Craig, Stephen ; Dion, Mark ; Dörner, Michael ; Droese, Felix ; Fischer, Christoph ; Fischer, Lothar ; Friedmann, Gloria ; Gerz, Jochen ; Giese, Tita ; Graham, Dan ; Finlay, Ian Hamilton ; Hellinger, Horst ; Hrdlicka, Alfred ; Huber, Stephan ; Immendorff, Jörg ; Kahl, Margrit ; Kellner, Rolf ; Kern, Stefan ; Kummer, Raimund ; Lang, Volker ; LeWitt, Sol ; Lorenz, Heike ; Mohr, Sabine ; Oldendorf, Rainer ; Otto, Waldemar ; Penck, A.R. ; Rändchen, Frank ; Richnow, Elisabeth ; Rückriem, Ulrich ; Schäfer, Christoph ; Schatte, Cornelia ; Schmidt Heins, Barbara ; Serra, Richard ; Shalev-Gerz, Esther ; Skene, Cathy ; Sleegers, Frank ; Stief, Ulrich ; Stricker, Thomas ; Trantel, Piet ; Ulrichs, Timm ; Walther, Franz Erhard ; Weiner, Lawrence ; Zaugg, Rémy
Duits
boek
Keywords: Hamburg